Adressing household wellbeing through maqasid shariah: a micro perspective / Sharifah Adlina Tuan Sayed Amran, Mohamed Saladin Abdul Rasool and Siti Mariam Ali - Tuan Sayed Amran, Sharifah Adlina; Abdul Rasool, Mohamed Saladin; Ali, Siti Mariam (Center for Islamic Philantrophy & Social Finance (CIPSF), 2019)
Wellbeing is defined as a situation of positive feeling (Happiness and satisfaction) and positive functioning elements (engagement and self-acceptance). Recent studies have shown wellbeing is conceptualized in a multidimensional form, explained in both objective and subjective perspective. From an Islamic perspective, wellbeing is explained through inside and outer fulfillment, driving towards a peaceful life, named as Hayat-e-Tayyaba. The objective of the vision of wellbeing is to satisfy the material and non-material needs. The maqasid al shariah principles are normally used by scholars to explain wellbeing in the Islamic perspective. The objective of this empirical paper is to present Islamic Household wellbeing Index (IHWI) using the five dimensions of maqasid al shariah. The present study employs 35 experts in identifying the five dimensions and the variables of the IHWI. The formulation of the IHWI is deliberated and its interpretation is highlighted.